Comparative genomics of Lentilactobacillus buchneri reveals strain-level hyperdiversity and broad-spectrum CRISPR immunity against human and livestock gut phages - Ismail Gumustop; Ibrahim Genel; Ibrahim Cagri Kurt; Fatih Ortakci (PLoS ONE, 2025)
This study conducted a comparative genomic investigation of 40 strains of Lentilactobacillus buchneri isolated from various environments—including fermented foods, silage, cattle rumen, and the nasopharynx—to identify species-level diversity and assess their CRISPR immunity. An average genome size of 2.55 ± 0.07 Mb, a GC content of 44.18 ± 0.15%, and 2444 ± 83 coding sequences were identified. Prophages were found in all strains except for two, while 17 strains contained plasmids. No genes associated with bacteriocins were identified. CRISPR analysis revealed the presence of 42 Type II-A and 45 Type I-E systems, with each strain having at least one Type II-A system (~ 2 systems per strain). Among the 33 tested strains, 29 encoded complete LbCas9 proteins, consisting of 1371 amino acids. In-silico analysis of PAM in Type II-A systems revealed a 5’-DNAWDHV-3’ motif, with a noted preference for 5’-AAAA-3’ at positions 3–6. The spacers found in CRISPR arrays targeted proteins involved in plasmid mobilization as well as components of phage tails, indicating their roles in inhibiting horizontal gene transfer and providing defense against phages. Remarkably, 27 spacers from 24 strains were found to match phages associated with human gut microbiomes, with several showing the ability to cross-target phages from livestock, kefir, and wastewater. This research expands the genomic understanding of L. buchneri from 10 to 40 genomes, uncovering the dynamics of CRISPR-phage co-evolution. The defined PAM preferences of the identified CRISPR systems, together with the broad predicted target range of their spacers, highlight their potential for biotechnological applications—most notably targeted CRISPRization of L. buchneri strains and in-silico-guided phage control during fermentation. These findings deepen our understanding of the ecological adaptability of L. buchneri and provide a foundation for future industrial exploitation of its native CRISPR immunity.